Oxygen related defects and vacancy clusters identified in sputtering grown UOx thin films by positron annihilation techniques - Macchi, Carlos Eugenio (2021)
We experimentally studied the formation of vacancy clusters and oxygen related defects in uranium oxide (UOx) thin films (<70 nm) changing the stoichiometry in the x = 2.2?3.5 range. Films were deposited on Si(0 0 1) by DC magnetron sputtering varying the substrate temperature (room temperature, 400 °C and 600 °C) and different relative O2 partial pressures in the argon-oxygen mixture. The different species of vacancy-like defects are identified by the combination of depth dependent positron annihilation techniques and by comparison of the experimental data with ab-initio calculations. In samples growth up to 400 °C substrate temperature, di- and tri- vacancies were formed whereas at higher temperature, hexa-vacancies and larger vacancy clusters appear. Film growth at increasing oxygen partial pressure was found not to be correlated with an increase of oxygen defects, but with the formation of more complex vacancy clusters. The presence of oxygen related defects is revealed by identifying preferential positron annihilations with oxygen electrons. Moreover, uranium vacancies inside vacancy clusters are identified by localization of positrons, in agreement with ab-initio calculations.